Comparison of uptake 99mTcO4; 99mTc-DTPA and 99mTc-MDP by breast cancer cell line. - Rafzi, Siti Noraisyah (Universiti Sains Malaysia, 2015)
The aim of this study is to determine the percentage uptake of different tracer by the breast cancer cell line (MCF-7), hence finding the optimum condition for the cells to absorb the radiopharmaceuticals. In addition, this study is to investigate the number of cell viable for different radioactivity with different type of tracers used. In the other hand, this study also to show the reliability and applicability of well counter in measuring different activity of tracer. 100k number of MCF-7 cell lines were prescribed with 100, 200, 300, 400, and 500 µCi of 99mTc-MDP, 99mTc-DTPA and 99mTc04 inside 6-well plate and incubated for an hour at 37°C. After the incubation finished, the cells were washed with phosphate buffer saline solution (PBS) to remove the extracellular tracers (99n'Tc-MDP,99mTc-DTPA and 99mTc04') suspended in the cell media, leaving cells monolayer to detach them from the well's bottom, so that the cells can be transferred into centrifuge tubes. Trypsine was added into the cell monolayers to detach the from the well's bottom. The measurement of activity of the cells and the washed media were taken by using well-counter. The percentage uptake of 99mTc-MDP, 99mTc-DTPA and 99mTcOf into cells was calculated and analyzed. Both 99mTc-DTPA and 99mTc-MDP shows the same pattern of percent intercellular uptake. While, TcO4 shows different pattern of percent intercellular uptake. All of the tracers (99mTc-MDP, 99mTc-DTPA and 99mTc04) have optimum uptake in the range of 200 µCi to 400 µCi. The percentage uptake of 99mTc-MDP, 99mTc-DTPA and 99mTc04 are 66.04%, 65.91% and 44.06%,. The number of cell viable (cell count/mL) for each tracer was found to be reduced as the activity increased. It was highlighted that different radioactivity used (µCi) give different intercellular uptake measured from each tracer. Different radioactivity used (µCi) also affected the number of cell viability for each tracer. In future, for study of cell uptake by using well-counter with wipe test software is not so applicable as it show high sensitivity toward low radioactivity. The acceptance counting activities is up to approximately 37 kBq.